Interactions Between Atmospheric Aerosols and Marine Boundary Layer Clouds on Regional and Global Scales - Wang, Zhen (The University of Arizona., 2018)
Airborne aerosols are crucial atmospheric constituents that are involved in global climate change and human life qualities. Understanding the nature and magnitude of aerosol-cloud-precipitation interactions is critical in model predictions for atmospheric radiation budget and the water cycle. The interactions depend on a variety of factors including aerosol physicochemical complexity, cloud types, meteorological and thermodynamic regimes and data processing techniques. This PhD work is an effort to quantify the relationships among aerosol, clouds, and precipitation on both global and regional scales by using satellite retrievals and aircraft measurements. The first study examines spatial distributions of conversion rate of cloud water to rainwater in warm maritime clouds over the globe by using NASA A-Train satellite data. This study compares the time scale of the onset of precipitation with different aerosol categories defined by values of aerosol optical depth, fine mode fraction, and Ångstrom Exponent. The results indicate that conversion time scales are actually quite sensitive to lower tropospheric static stability (LTSS) and cloud liquid water path (LWP), in addition to aerosol type. Analysis shows that tropical Pacific Ocean is dominated by the highest average conversion rate while subtropical warm cloud regions (far northeastern Pacific Ocean, far southeastern Pacific Ocean, Western Africa coastal area) exhibit the opposite result. Conversion times are mostly shorter for lower LTSS regimes. When LTSS condition is fixed, higher conversion rates coincide with higher LWP and lower aerosol index categories. After a general global view of physical property quantifications, the rest of the presented PhD studies is focused on regional airborne observations, especially bulk cloud water chemistry and aerosol aqueous-phase reactions during the summertime off the California coast. Local air mass origins are categorized into three distinct types (ocean, ships, and land) with their influences on cloud water composition examined and implications of wet deposition discussed. Chemical analysis of cloud water samples indicates a wide pH range between 2.92 and 7.58, with an average as 4.46. The highest pH values were observed north of San Francisco, coincident with the strongest land mass influence (e.g. Si, B, and Cs). Conversely, the lowest pH values were observed south of San Francisco where there is heavy ship traffic, resulting in the highest concentrations of sulfate, nitrate, V, Fe, Al, P, Cd, Ti, Sb, P, and Mn. The acidic cloud environment with influences from various air mass types can affect the California coastal aquatic ecosystem since it can promote the conversion of micronutrients to more soluble forms. Beyond characterization of how regional air mass sources affect cloud water composition, aircraft cloud water collection provides precious information on tracking cloud processing with specific species such as oxalic acid, which is the most abundant dicarboxylic acid in tropospheric aerosols. Particular attention is given to explore relationship between detected metals with oxalate aqueous-phase production mechanisms. A number of case flights show that oxalate concentrations drop by nearly an order of magnitude relative to samples in the same vicinity with similar environmental and cloud physical conditions. Such a unique feature was consistent with an inverse relationship between oxalate and Fe. In order to examine the hypothesis that oxalate decreasing is potentially related to existing of Fe, chemistry box model simulations were conducted. The prediction results show that the loss of oxalate due to the photolysis of iron oxalato complexes is likely a significant oxalate sink in the study region due to the ubiquity of oxalate precursors, clouds, and metal emissions from ships, the ocean, and continental sources.